PENGEMBANGAN MEDIA FLASHCARD UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR PADA MATERI KLASIFIKASI HEWAN VERTEBRATA DAN INVERTEBRATA - Nurma Yunita, Shintya; Julianto; Nur Aisyah, Marista (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is one of the essential twenty-first century skills that should be developed through science and social studies (IPAS) learning in elementary schools. However, preliminary observations in Grade III of SDN Kedurus 1 Surabaya revealed that students experienced difficulties in understanding the classification of vertebrate and invertebrate animals and demonstrated low critical thinking skills. This study aimed to develop the flashcard PAPINKLA (Classification Smart Board) learning media and to determine its validity, practicality, and effectiveness in improving students' critical thinking skills. This study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were Grade III students of SDN Kedurus 1 Surabaya, with Class III-B as the experimental group and Class III-C as the control group. Data were collected through observations, interviews, questionnaires, and tests and analyzed using descriptive and inferential statistics. The results showed that flashcard PAPINKLA achieved a very high level of validity, with material and media validation scores of 92.87% and 90%, respectively. The practicality level reached 92.72% based on the teacher's responses and 94.28% based on students' responses, both categorized as very practical. The effectiveness test indicated a high average N-Gain score of 0.71 in the experimental class, while the Independent Samples t-test yielded a significance value of p < 0.05, indicating a significant difference compared to the control class. Therefore, flashcard PAPINKLA is considered valid, practical, and effective in enhancing elementary school students' critical thinking skills in IPAS learning.